We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
31
1
avatar

Simplify and rationalize the denominator: $\sqrt[3]{\frac{8}{\sqrt{27}}}.$ If the simplified expression can be expressed in the form $\frac{a\sqrt{b}}{c}$, what is $a + b + c$?

 Jun 12, 2019

Best Answer 

 #1
avatar+8207 
+2

\(\sqrt[3]{\frac{8}{\sqrt{27}}}\ =\ \Bigg(\frac{8}{27^{\frac12}}\Bigg)^{\frac13}\ =\ \frac{8^{\frac13}}{27^{\frac12\cdot\frac13}}\ =\ \frac{8^{\frac13}}{27^{\frac13\cdot\frac12}}\ =\ \frac{8^{\frac13}}{(27^{\frac13})^{\frac12}}\ =\ \frac{2}{3^{\frac12}}\ =\ \frac{2}{\sqrt3}\ =\ \frac{2}{\sqrt3}\cdot\frac{\sqrt3}{\sqrt3}\ =\ \frac{2\sqrt3}{3}\)

 

Now it is simplified in the form  \(\frac{a\sqrt{b}}{c}\) .

 

a + b + c  =  2 + 3 + 3  =  8

 Jun 12, 2019
 #1
avatar+8207 
+2
Best Answer

\(\sqrt[3]{\frac{8}{\sqrt{27}}}\ =\ \Bigg(\frac{8}{27^{\frac12}}\Bigg)^{\frac13}\ =\ \frac{8^{\frac13}}{27^{\frac12\cdot\frac13}}\ =\ \frac{8^{\frac13}}{27^{\frac13\cdot\frac12}}\ =\ \frac{8^{\frac13}}{(27^{\frac13})^{\frac12}}\ =\ \frac{2}{3^{\frac12}}\ =\ \frac{2}{\sqrt3}\ =\ \frac{2}{\sqrt3}\cdot\frac{\sqrt3}{\sqrt3}\ =\ \frac{2\sqrt3}{3}\)

 

Now it is simplified in the form  \(\frac{a\sqrt{b}}{c}\) .

 

a + b + c  =  2 + 3 + 3  =  8

hectictar Jun 12, 2019

9 Online Users

avatar